EL HALLAZGO DEL PRIMER NIDO DE DINOSAURIOS TRIASICOS, (SAURISCHIA, PROSAUROPODA), TRIASICO SUPERIOR DE PATAGONIA, ARGENTINA (Ameghiniana, 2013)
Several in complete skeletons of juvenile Prosauropoda and two eggs were recovered from Upper Triassic beds of Southern Patagonia. The specimens are refered to a new genus and species, Mussaurus patagonicus, showing a mixed picture of anatomical affinities. Fore lirnbs, pelvis and hind limb are tipically Prosauropoda; the short cervical vertebrae resemble those of the Middle Triassic thecodont Lagosuchus, and some characters of the skull suggest relationships with both Prosauropoda and Sauropoda. Tentatively a new family of Prosauropoda is proposed to include this new species.